2019
DOI: 10.1007/s11332-019-00552-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-volume high-intensity interval training and circuit training on maximal oxygen uptake

Abstract: Purpose High-intensity interval training (HIIT) and circuit training (CT) are popular methods of exercise, eliciting improvements in cardiorespiratory fitness (CRF). However, direct comparisons of these two training methods are limited. We investigated the effects of HIIT and CT on CRF. Methods Thirty-nine apparently healthy middle-aged participants [HIIT; mean age: 42.5 ± 12.3; V O 2max 31.5 ± 7.1 (ml kg −1 min −1); 52% males; CT; mean age: 41.2 ± 12.9; V O 2max 31.4 ± 6.8 (ml kg −1 min −1); 57% males] were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
4
0
2
Order By: Relevance
“…The greater VO 2max improvement in HIIT group vs. MICT suggests that exercise intensity, more than volume, is a critical aspect of training adaptations [ 33 ]. Our findings are in line with previous studies reporting that HIIT training led to a greater improvement in VO 2max when compared to traditional circuit training [ 34 ] and similarly to that obtained with MICT protocols [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The greater VO 2max improvement in HIIT group vs. MICT suggests that exercise intensity, more than volume, is a critical aspect of training adaptations [ 33 ]. Our findings are in line with previous studies reporting that HIIT training led to a greater improvement in VO 2max when compared to traditional circuit training [ 34 ] and similarly to that obtained with MICT protocols [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another finding in this study is the effective Circuit weight training program to increase the VO2max endurance component Sonchan, Moungmee, and Sootmongkol (2017) found that after 8 weeks of the Circuit training program, anaerobic capacity and cardiovascular endurance significantly increased (P<0,05) (Birkett et al, 2019).…”
Section: The Effects Of Circuit Weight Training For Physical Fitnessmentioning
confidence: 50%
“…HIIT has been promoted as a superior, time-saving exercise strategy to enhance CRF in the middle-aged [98]. A systematic review of evidence suggested that both interval training and MICT could significantly improve CRF in middle-aged and elderly people; however, MICT has no significant effect on improving VO 2max in middle-aged compared with HIIT and sprint interval training.…”
Section: Middle-aged (Ages 45-59 Years) Adultsmentioning
confidence: 99%